Deciphering the differences of bacterial communities between high- and low-productive wheat fields using high-throughput sequencing - Niu, Hongjin; Yuan, Min; Chen, Xiaobo; Zhao, Jingwei; Cui, Yushuang; Song, Yao; Zhou, Sihao; Song, Alin; Huang, Yali (Frontiers in Microbiology, 2024)
Microbial communities have been demonstrated to be essential for healthy and productive soil ecosystems. However, understanding of the relationship between soil microbial community and soil productivity levels is remarkably limited. In this study, the bulk soil (BS), rhizosphere soil (RS), and root (R) samples from the historical high-productive (H) and low-productive (L) soil types of wheat in Hebei province of China were collected and analyzed by high-throughput sequencing. The study highlighted the richness, diversity, and structure of bacterial communities, along with the correlation networks among different bacterial genera. Significant differences in the bacterial community structure between samples of different soil type were observed. Compared to the low-productive soil type, the bacterial communities of samples from the high-productive soil type possessed high species richness, low species diversity, complex and stable networks, and a higher relative abundance of beneficial microbes, such as Pseudoxanthomonas, unclassified Vicinamibacteraceae, Lysobacter, Massilia, Pseudomonas, and Bacillus. Further analysis indicated that the differences were mainly driven by soil SOM (soil organic matter), AN (available nitrogen), and EC (electrical conductivity). Overall, the soil bacterial community are important factor affecting the soil health and crop production, which provides a theoretical basis for the targeted regulation of microbes in low-productivity soil types.